Kedudukan Notaris sebagai Mediator dalam Penyelesaian Sengketa Kenotariatan - Hedy Faizal; Indratirini Indratirini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The position of a notary has experienced development and evolution along with changes in society, technology and the legal system. Notaries have taken a more significant role in digital transactions and documents. Notaries can play a role in dispute resolution as mediators or intermediaries in several situations. This is possible in situations where the parties involved in the dispute agree to find a solution together under the guidance of a notary. Notaries can act as mediators in the mediation process. Mediation is a process that involves the disputing parties meeting with a neutral notary, who helps them communicate, negotiate, and find a solution together. The aim of this research is to explain the position of notaries as mediators in resolving notarial disputes. The approach used in this research is a juridical-empirical approach. The results of this research are the position of the notary as a mediator in resolving notarial disputes where the role of the mediator acts as a neutral facilitator in resolving disputes between the parties involved in notarial matters. The notary who acts as a mediator must remain neutral and not take sides with either party in the dispute. They should have no personal or professional interest in the outcome of the dispute. The notary as a mediator will adopt a mediation approach which usually involves a communicative and collaborative approach. They will strive to create an environment that allows parties to talk, listen, and reach mutual agreements.